Regional strategy for patient safety in the WHO South-East Asia Region (2016–2025) - World Health Organisation (World Health Organisation, 2021)
The quality and safety of health care is a major concern of ministries of health in the South-East Asia Region. Governments are responsible for ensuring health services are safe and of good quality. Patient safety is an essential aspect of health-care quality. It includes preventing medical errors that may lead to adverse events and harm. The safety of the patient has to be kept in mind for all types of care and at all levels of care. As new health interventions have become more complex, the risk and potential for harm has increased. Evidence shows that harm to patients is almost always a result not of failures of an individual health-care provider alone, but of a chain of failures in a health-care organization’s operations as a whole. Therefore, it is of paramount importance that a systems approach to patient safety is adopted. Ensuring the quality and safety of health care is an enormous challenge for frontline health workers, health facility managers and ministries of health responsible for policy and regulatory frameworks. Towards this end, governments in Member States are adopting a range of policies, strategies and methods to improve patient safety, including strengthening related legislation and regulations. Patient safety has been recognized as a growing international public health problem since 2002, when the World Alliance for Patient Safety was formed. In 2006, the Regional Committee of South-East Asia Region endorsed a resolution on patient safety. The World Health Organization has developed guidelines, checklists and programmes to ensure quality and safety of health care and minimize health care-acquired infections, antimicrobial resistance and medical mismanagement as well as reduce hazards from clinical and biological waste. These can be used by Member States in their efforts to improve patient safety. The need for national patient safety strategies has also been emphasized. To support the development of national patient safety strategies within the Region, an ad-hoc expert working group has developed this regional strategy. This has been endorsed by all Member States. It sets out six clear objectives that provide guidance for improving the quality and safety of health care in our Region.